Hizbul Wathan Uniform Policy as a Media for Instilling Discipline at Muhammadiyah Elementary School Kleco Kotagede Yogyakarta - Arrizky Yogi Maulana (Journal of Indonesian Progressive Education, 2024)
The Hizbul Wathan Scout Movement is a forum for effective character development in the school environment, which consists of Muhammadiyah cadres who are trained to carry out the preaching of ar maruf and nahi munkar. This article explains that there is an interesting policy at SD Muhammadiyah Kleco Kotagede Yogyakarta which may not be found in other schools, namely the Hizbul Wathan uniform policy of wearing full attributes from morning/entering school until leaving school/after the HW extracurricular is finished. This journal uses a type of qualitative research, namely this research uses a literature study method, namely research by reviewing various literature studies that are relevant to the research topic. Students are able to learn lessons about discipline, a sense of responsibility, and a sense of not complaining through small things. By getting used to these things, students will be more appreciative of all the rules that apply in the environment around them